Northwestern and Other Historical Vignettes regarding the Vascular Anastomotic Coupling Device - Dumanian, Gregory A. (Plast Reconstr Surg Glob Open, 2019)
The vascular anastomotic coupling device is a widely used and effective aid to reconstructive microsurgery. Although there is a long history of innovators connected with this device, the current design of 6 interdigitating holes and pins was created de novo by a Northwestern medical student in 1960.